2018
DOI: 10.14368/jdras.2018.34.4.280
|View full text |Cite
|
Sign up to set email alerts
|

Influence of crown-to-implant ratio of short vs long implants on implant stability and marginal bone loss in the mandibular single molar implant

Abstract: The purpose of this randomized clinical trial is to determine whether implant length and the crown-to-implant (C/I) ratio influence implant stability and peri-implant marginal bone loss (MBL). Materials and Methods: 46 patients with single tooth missing in the posterior molar region of the mandible were included in this study. 19 implants (CMI IS-III active ® long implant) of 5.0 mm diameter and 10 mm length were installed for the control group, while 27 implants (CMI IS-III active ® short implant) of 5.5 mm d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Baek et al found that the ISQ values of patients with short implants were not significantly different from those of patients with regular implants, suggesting that the length of the implant did not affect its stability and prognosis [ 24 ]. Bischof et al reported that primary implant stability demonstrated significant differences depending on the bone quality; however, implant diameter and length did not affect the primary implant stability [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Baek et al found that the ISQ values of patients with short implants were not significantly different from those of patients with regular implants, suggesting that the length of the implant did not affect its stability and prognosis [ 24 ]. Bischof et al reported that primary implant stability demonstrated significant differences depending on the bone quality; however, implant diameter and length did not affect the primary implant stability [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, proper implantation torque could not be achieved owing to poor bone quality, resulting in the elimination of the fixture and an inability to perform the experiment. Baek et al found that the ISQ values of patients with short implants were not significantly different from those of patients with regular implants, suggesting that the length of the implant did not affect its stability and prognosis [21]. Bischof et al reported that primary implant stability demonstrated significant differences depending on the bone quality; however, implant diameter and length did not affect the primary implant stability [22].…”
Section: Discussionmentioning
confidence: 99%